2012
DOI: 10.3109/00365599.2012.700946
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress assessment of patients suffering from prostate cancer

Abstract: Anxiety and depression as well as concerns about a negative effect on their partnership were shown to play a minor role in patients during the interval between PB and RP, while distress and concerns about erectile dysfunction and urinary incontinence were more prevalent. Support from the patient's medical and social environment and a sound partnership may have a protective effect on emotional status. Waiting time for surgery exceeded the patients' tolerated time-frames and may further contribute to the psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The varied evidence for the association of waiting times with short- and longer-term outcomes implies that the cut off times of these targets are somewhat arbitrary, with 31 and 62 days having little biological relevance: indeed, some studies point out the difficulty of showing a difference in outcomes that depends on short time differences [ 26 , 30 ]. However, there is general agreement that intervals between referral, diagnosis and treatment should be minimised, as every effort should be made to reduce the anxiety experienced by patients while waiting, however long that is [ 8 – 10 , 24 , 29 ]. Murchie et al point out that the publicity surrounding waiting times could itself engender anxiety when patients have to wait past the ‘cut-off’ [ 27 ], and this anxiety can have wider impacts: a recent study reported the highest mortality rates among the most distressed cancer patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The varied evidence for the association of waiting times with short- and longer-term outcomes implies that the cut off times of these targets are somewhat arbitrary, with 31 and 62 days having little biological relevance: indeed, some studies point out the difficulty of showing a difference in outcomes that depends on short time differences [ 26 , 30 ]. However, there is general agreement that intervals between referral, diagnosis and treatment should be minimised, as every effort should be made to reduce the anxiety experienced by patients while waiting, however long that is [ 8 – 10 , 24 , 29 ]. Murchie et al point out that the publicity surrounding waiting times could itself engender anxiety when patients have to wait past the ‘cut-off’ [ 27 ], and this anxiety can have wider impacts: a recent study reported the highest mortality rates among the most distressed cancer patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervals between referral for suspicion of cancer, confirmation of diagnosis and beginning of treatment are indicators of quality in cancer care: the time patients have to wait between these events have been scrutinised for many years [ 1 7 ]. Delays in waiting times have the potential both to induce worry and anxiety, which worsens patient experience [ 8 – 10 ], and to influence patient outcomes [ 11 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of prostate cancer often focus on functional outcomes of therapy, the extent to which adverse effects bother men also needs careful evaluation (Luckett et al , 2009; Pachman et al , 2012; Seklehner et al , 2012). Understanding the importance of comprehensive patient outcomes is essential in delivering whole-patient cancer care (Jacobsen et al , 2012; Stanton, 2012).…”
mentioning
confidence: 99%
“…Previous studies regarding the psychological impact of prostate biopsy have reported variable results ranging from no apparent impact to most patients experiencing anxiety. [25,26] Various strategies have been suggested to reduce the psychological distress of the procedure. Wade et al [26] noted that accurate prebiopsy counseling and reassurance of the normality of some side effects (eg, hematuria, hematospermia) after prostate biopsy reduced the psychological distress (anxiety) caused by side effects.…”
Section: Discussionmentioning
confidence: 99%